Electric fuses : fundamentals and new applications - Nurse, Nigel P. M.; Wright, A.; Newbery, P. G. (IET energy engineering series, 2022)
This 4th edition of the classic reference on electric fuses has been substantially updated. The contents, data, descriptions and illustrations have been revised, and new topics added including fuses for photovoltaic systems, battery storage and electric vehicles.